Approximation by Szász-Jakimovski-Leviatan-Type Operators via Aid of Appell Polynomials. (18th September 2020) - Nasiruzzaman, Md.; Aljohani, A. F.
Abstract : The main purpose of the present article is to construct a newly Szász-Jakimovski-Leviatan-type positive linear operators in the Dunkl analogue by the aid of Appell polynomials. In order to investigate the approximation properties of these operators, first we estimate the moments and obtain the basic results. Further, we study the approximation by the use of modulus of continuity in the spaces of the Lipschitz functions, Peetres K-functional, and weighted modulus of continuity. Moreover, we study A -statistical convergence of operators and approximation properties of the bivariate case.